2012
DOI: 10.5012/bkcs.2012.33.8.2619
|View full text |Cite
|
Sign up to set email alerts
|

A Green Protocol for the Bromination and Iodination of the Aromatic Compounds using H5IO6/NaBr and H5IO6/NaI in the Water

Abstract: Bromination and iodination of the aromatic compounds have efficiently been carried out at room temperature and 70 o C, respectively, in short reaction times using orthoperiodic acid/sodium bromide (1:2) and orthoperiodic acid/sodium iodide (1:2) in water to prepare the corresponding halo compounds with excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The only article describing the use of iodate to oxidatively brominate aromatics was by Khazaei et al ., who obtained, apart from statistically insignificant variation, identical results as their previous article performing identical reactions; however, using sodium periodate instead of sodium iodate [141–142] . Later, periodate and iodate were compared with the equivalent iodination [138c] …”
Section: Sodium Periodatesupporting
confidence: 51%
“…The only article describing the use of iodate to oxidatively brominate aromatics was by Khazaei et al ., who obtained, apart from statistically insignificant variation, identical results as their previous article performing identical reactions; however, using sodium periodate instead of sodium iodate [141–142] . Later, periodate and iodate were compared with the equivalent iodination [138c] …”
Section: Sodium Periodatesupporting
confidence: 51%
“…One of the most effective solutions to this situation is the use of iodonium equivalents (I + ), for example, N-iodosuccinimide, [7] Niodosaccharin, [8] iodine monochloride [9] and IOAc. [10] Another effective solution is the oxidative activation strategy where the electrophilic I + -type species is generated through oxidation of iodine sources by oxidizing reagent systems, for example, CrO 3 , [11] PbA C H T U N G T R E N N U N G (OAc) 4 , [12] CeA C H T U N G T R E N N U N G (OTf) 4 , [13] hydrogen peroxide, [14] H 5 IO 6 , [15] peroxodisulfate salts, [16] and ferrate salts. [17] The use of molecular oxygen as the oxidant is a still desirable goal from environmental and economic perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Hou J. et al have reported [10] about an ecologically safe method of bromination of 4-nitroaniline (scheme 6) at room temperature, by use of the I2O5KBr water system. The bromination of aromatic amines in CH2Cl2/H2O with HJO3/KBr [11] and in water with ortho-periodic acid / sodium bromide (1: 2) (scheme 7) [12] has been carried out at room temperature for a short time. The bromination of various substituted anilines with oxone and sodium bromide (scheme 8) has been carried out [13] while stirring at room temperature, solutions of anilines, oxone and sodium bromide in 1:1 mixture of CH3CN/H2O.…”
Section: Scheme 4 схема 4 Scheme 5 схемаmentioning
confidence: 99%